New archosaur remains from the portezuelo formation (turonian– coniacian, upper cretaceous) of “Los Bastos” locality (Senillosa, Neuquén province, Argentina) - Bellardini, Flavio (2020)
In the central Neuquén Basin, the Portezuelo Formation is represented with extended fluvial outcrops, many of whom are well-known for yielded an abundant vertebrate fossil record. In this contribution we report new archosaur remains from “Los Bastos” locality (Neuquén Province, Patagonia, Argentina), which here are preliminary assigned to pterosaur, sauropod and theropod dinosaurs. Most of the fossils were found associated in situ in a well-cemented paleosoil composed by coarsegrained and browned sandstones, while other isolated materials were recovered few hundred meters away. Most relevant sauropod elements are: a fragmentary cone-chisel-like tooth with single high-angled wear-facet (MMS-PV-20), two procoelic anterior caudal vertebrae with neural arch beyond the anterior articular surface (MMS-PV-09-10), and a femur with anteroposteriorly well-compressed diaphysis and a prominent lateral bulge (MMS-PV-15). According to size and diagnostic features of each element we tentatively refer these bones to Titanosauria indet. Other materials are an incomplete theropod humerus (MMS-PV-18) with an internal tuberosity connected with humeral head and a low great tubercle, and four incomplete weakly-amphicoelous dorsal centra, with a shallow lateral fossa, which we assigned to Theropoda indet. (MMS-PV-22, 23, 24). An incomplete femur of a large pterosaur specimen (MMS-PV-21) with a wellmarked lesser trocanther and thin bone-wall was also found. In the “Los Bastos” locality, the Portezuelo Formation is associated to a meandering, high-sinuosity fluvial environment, as well as in type-locality. These new archosaur materials increase the Portezuelo Formation vertebrate fossil record for central Patagonia, and improve the faunal diversity regarded for Los Bastos locality of south Neuquén Province.